The Emergence of African literature in the public space of French Equatorial Africa : the case of the cultural magazine Liaison - (:unkn) unknown (My University, 2014)
Periodicals such as Liaison, L’Etoile de l’AEF or La Semaine de l’A.E.F. played a fundamental role in what H.J. Lüsebrink called “the conquest of the public space” by the colonised elites, in this case those of French Equatorial Africa (Gabon, Middle Congo, Ubangui Shari and Chad), and in particular, in the constitution of a local literary field. Since 1950, there was a profusion of journals, thanks to the colonial press which managed the rare printing presses and publishing houses of the continent. This study examines the influence of the press on the birth of the first African works, especially for the Frech Equatorial Africa of this time. It refers to a founding era of the African literary history, still too little really studied to day. Although, it is not centered as often on books, but on periodicals which are essential keys for any historical approach of literary life
Keywords: African Research